THE IMPORTANCE OF THE PLAY MATERIALS IN THE AUTISTIC CHILD’S LEARNING - Steffane Silva de Lima, Djessyca (Revista Gênero e Interdisciplinaridade, 2024)
The Autism is a Pervasive Developmental Disorder characterized by difficulties in the areas of social interaction, communication and behavior. The Autism has no cure, it is generally diagnosed after the age of three and its treatment seeks to bring a better quality of life to the autistic person. Autistic children have difficulty learning in the traditional way, so it is important that teachers give new meaning to the way they teach, using playful materials for more pleasurable and meaningful learning. In this sense, this research sought to verify how the teaching and learning process of children with autism takes place. To do this, it is important to understand what autism is; analyze how the learning process occurs in children with autism and understand the role of play in the learning of children with autism. This research is characterized as qualitative, as it addresses issues that cannot be quantified; To answer the proposed questions and objectives, a bibliographic study will be carried out, based on books and articles relating to the topic; The research is exploratory in nature, so that it is possible to have a global view of the work, as well as its usefulness for research. Therefore, this work is relevant as it can contribute to reflection on the part of society, educators and family members about how the learning process of children with autism takes place and the importance of playfulness in this regard, enabling a new perspective. about education for children with autism.